2020
DOI: 10.2147/cmar.s263010
|View full text |Cite
|
Sign up to set email alerts
|

<p>Programmed Death-1 Receptor (PD-1) as a Potential Prognosis Biomarker for Ovarian Cancer Patients</p>

Abstract: Aim: Ovarian cancer (OC) is one of the most lethal gynecological malignancies. Recent studies suggest a crucial role of the PD-1/PD-L1 pathway in OC pathogenesis. Therefore, our study aimed at evaluation of the clinical importance of PD-1 expression in ovarian cancer patients. Patients and Methods: In this study, we investigated the role of PD-1 in OC patients (n=50) by analyzing its expression on CD4 + and CD8 + T cells in three OC environments: peripheral blood (PB), peritoneal fluid (PF), and tumor (TT) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…In our previous study, we established the sPD-1 level in the plasma and PF of ovarian cancer patients and its correlations with clinical data and patient outcomes [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we established the sPD-1 level in the plasma and PF of ovarian cancer patients and its correlations with clinical data and patient outcomes [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we found that OC patients with a lower soluble PD-1 level in the plasma, but not in PF ( p > 0.05), had beneficial 5-year survival than those with a higher sPD-1 concentration [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An original study suggested that higher PD-1 level in the plasma could be a predictive biomarker and predicted poor survival of OC patients. 40 In addition, a recent study by Kim et al showed that PD-L1 expression levels in tumor cells, intraepithelial tumor-infiltrating lymphocytes, and stromal tumor-infiltrating lymphocytes were correlated with a better prognosis in SC. 41 Interestingly, our results showed a high PD-L1 expression in CCC, implying poor prognosis, supporting the analysis of PD-L1 expression in this specific histological subtype with a potential benefit of targeted therapy.…”
Section: Discussionmentioning
confidence: 98%